The Relationship of Lifestyle to Hypertension in Young Adults: A Cross-Sectional Study - Inglee Lala Roring; Ivon Kristiawati Banggiling; Redita Elok Winanti; Evanny Indah Manurung; Ester Silitonga (Indonesian Journal of Global Health Research, 2024)
Hypertension is called the silent killer because it occurs without any complaints, it is a type of non-communicable disease. Lifestyle is an individual's life pattern expressed in his interests, activities, and opinions that are influenced by the environment, daily behavior and individual functions in work, activities, and pleasure. One of the factors causing hypertension is lifestyle. Objective to determine the relationship between lifestyle and the incidence of hypertension in young adults in the community in one of the urban villages in Tangerang Regency. Research methods using a correlational quantitative method with a cross-sectional research design. The population in this study were one of the urban villages in Tangerang Regency with an age range of 18-40 years and the sample was selected using purposive sampling. The research instruments used were lifestyle questionnaires and PSQI. Data analysis used univariate and bivariate analysis using the Spearman correlation test. Results showed that there was no relationship between lifestyle and the incidence of hypertension, but there was 1 indicator in lifestyle that had a relationship with the incidence of hypertension, namely smoking with (p-value = 0.013). Respondents are expected to maintain a good lifestyle such as physical activity, diet, not smoking and not consuming alcohol, and respondents can improve sleep patterns to continue to have an overall healthy lifestyle.